Protocol for a randomised controlled trial of a family strengthening program to prevent unhealthy weight gain among 5 to 11-year-old children from at-risk families: the Strong Families Trial - Cristy Brooks; Catherine Helson; Madalyn McCormack; Louise A Baur; Timothy Gill; Julie Green; Baki Billah; Paula Cronin; Anoop Johar; Jennifer Plaskett; Michelle Nolan; Monika Latanik; et al. (BMC, 2022)
Abstract Background Obesity is an increasing health concern in Australia among adult and child populations alike and is often associated with other serious comorbidities. While the rise in the prevalence of childhood obesity has plateaued in high-income countries, it continues to increase among children from disadvantaged and culturally diverse backgrounds. The family environment of disadvantaged populations may increase the risk of childhood obesity through unhealthy eating and lifestyle practices. The Strong Families Trial aims to assess the effectiveness of a mixed behavioural and lifestyle intervention for parents and carers of at-risk populations, i.e. families from culturally diverse and disadvantaged backgrounds, in preventing unhealthy weight gain among children aged 5 to 11 years. Methods Eight hundred families from low socio-economic areas in Greater Western Sydney, NSW, and Melbourne, VIC, will be recruited and randomised into a lifestyle intervention or control group. The intervention comprises 90-minute weekly sessions for 6 weeks (plus two-booster sessions) of an integrated, evidence-based, parenting and lifestyle program that accounts for the influences of family functioning. Primary (anthropometric data) and secondary (family functioning, feeding related parenting, physical activity, consumption of healthy foods, health literacy, family and household costs) outcome measures will be assessed at baseline, immediately following the intervention, and 12 months post-intervention. Discussion This study will elucidate methods for engaging socially disadvantaged and culturally diverse groups in parenting programs concerned with child weight status. Trial Registration This study is registered with the Australian New Zealand Clinical Trials Registry ( ACTRN12619001019190 ). Registered 16 July 2019.